PENGUSIRAN NON-MUSLIM DI TANAH ARAB (Analisis Hermeneutik Hadis No. 1767 dalam Sahih Muslim) - Syachrofi, Muhammad; Masiyan, Masiyan; Haitomi, Faisal (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
One of the factors for the occurrence of acts of violence in the name of religion is inaccuracy in reading religious texts. One form of such inaccuracy is the literal reading of the Qur'an and the hadith of the Prophet (peace be upon him). For example, the hadith whose editorship says that the Prophet (peace be upon him) once drove non-Muslims out of the Arabian Peninsula. This hadith will impact rigid understanding and foster anti-Muslim attitudes if taken literally. Therefore, in this paper, the author tries to re-read these hadiths using hermeneutic analysis to find the contextual meaning of these hadiths. This literature research is carried out qualitatively by collecting data from primary and secondary sources which are then analyzed using a hermeneutic approach. The conclusion is that the hadith was delivered by the Prophet (peace be upon him) in the position of head of state so that the hadiths he delivered had implications for state issues, not creed issues. The expulsion was not directed at non-Muslims as a whole but only at specific individuals who could threaten the stability of Medina at that time.